Pronominal anaphora, coreference, and closed quotation marks. (31st August 2018) - Gasparri, Luca
Abstract : Consider the following sentence: "Mary meditated on the sentence 'Bill is a good friend' and concluded that he was a good friend." It is standardly assumed that in sentences of this sort, containing so‐called "closed" quotations, the expressions occurring between quotation marks are mentioned and do not take their ordinary referents. The quoted NP "Bill" refers, if anything, to the name 'Bill, ' not to the individual Bill. At the same time, the pronoun "he, " apparently anaphoric on quoted "Bill, " refers to the individual Bill. The case seems thus to invalidate the intuitive principle that pronouns anaphoric on referential expressions inherit their reference from their antecedents. The paper formulates the argument, argues that sentences exhibiting the described pattern do not constitute evidence against the intuitive principle, and proposes an alternative account of the anaphoric relation involved.